Analisis Pengaruh Brand Equıty, E-Wom, Dan Brand Image Darı Socıal Medıa Terhadap Purchase Intentıon Restoran Fast Food Dı Kota Batam - Erilia Kesumahati; Raymond Raymond (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2021)
This study aimed to analyze the effect of brand equity, E-WOM, and brand image from social media on the purchase intention of fast food restaurants in Batam City. The independent variables used in this study were social media, brand equity, E-WOM, and brand image. Meanwhile, purchase intention was used as the dependent variable. In this study, 306 respondents were used with the purposive sampling method through the distribution of online questionnaires. SPSS software version 26.0 and SmartPLS version 3.0 were used in the analysis of research data. The results of this study indicated that social media has significant positive effect on brand equity, E-WOM, and brand image. Then those three variables, namely brand equity, E-WOM, and brand image have significant positive effect on purchase intention. Based on the results of this study, it is clear that in this era of digital technology, business people can utilize social media as a means to increase brand equity, E-WOM, and brand image of a product or service.